2004
DOI: 10.1002/lt.20280
|View full text |Cite
|
Sign up to set email alerts
|

One-year morbidity after donor right hepatectomy

Abstract: Live donors are becoming an increasingly important source of donor organs in liver transplantation; however, long-term functional aspects of recovery from donor right hepatectomy are unknown. We analyzed donor outcomes at 1-year follow-up. We performed a single-center retrospective analysis of 70 right hepatectomy donors. Sixweek and 1-year postoperative follow-up results were compared to preoperative baseline values. Ultrasonography was performed in all donors at 6 weeks and as clinically indicated. All donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 8 publications
1
44
1
Order By: Relevance
“…Such analysis would not be possible or appropriate in programs with poor donor compliance to follow-up. 31 The results of this study reflected the temporary nature of the donors' disabilities. Some authors have suggested a 10-points change in any SF-36 domain or more than 10% change as being clinically meaningful.…”
Section: Discussionmentioning
confidence: 63%
“…Such analysis would not be possible or appropriate in programs with poor donor compliance to follow-up. 31 The results of this study reflected the temporary nature of the donors' disabilities. Some authors have suggested a 10-points change in any SF-36 domain or more than 10% change as being clinically meaningful.…”
Section: Discussionmentioning
confidence: 63%
“…The safety of living liver donors is of paramount importance and this issue has been aggressively discussed so far (10)(11)(12)(13)(14)(15)(16). Although the liver has a capacity to regenerate, it is generally believed that the larger the resected liver parenchyma is, the more frequently postoperative complications will occur (13,14,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the progress of surgical techniques and better postoperative follow-up, literature information shows that the incidence of healing failures has not changed in recent years 3,4,9 . Works suggest that posthepatectomy scars are less resistant than for other surgical procedures 4,7,18 . It was demonstrated that there is an increase in collagen synthesis in the remaining liver after partial hepatectomy until the 7 th day, this difference no more existing from the 14 th day on.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…Similar situation is described for patients undergoing partial hepatectomies. Rudow et al 7 reported an incidence of 20%, while D'Angelica et al 8 , 9.8%. According to Van't et al 9 , most severe situations with evisceration led 25% of patients to death within 60 days.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 96%